Effect of body weight and scrotal circumference on semen production traits in murrah buffalo bulls - P, RAMAJAYAN; SIVASELVAM, S N; KARTHICKEYAN, S M K; VENKATARAMANAN, R; GOPINATHAN, A; KULASEKAR, K (The Indian Journal of Animal Sciences, 2022)
The study was undertaken to determine the effect of bodyweight and scrotal circumference on semen production traitsin Murrah buffalo bulls. Data on seminal characteristics,body weight, and scrotal circumference collected from 77Murrah bulls were utilized to study the effects using leastsquareanalysis under General Linear Model. Body weightand scrotal circumference showed a highly significantimpact on all semen production traits. Similarly, thecorrelation coefficients were also highly significant andpositive, except the non-correlation between scrotalcircumference and post-thaw motility. An increasing trendin seminal parameters in rise with body weight and scrotalcircumference were also observed. Furthermore, bullsweighing 540 kg and above with scrotal circumference of>30 cm displayed better semen quality with higher numberof frozen semen doses per ejaculate. These findings suggestthat higher body weight and scrotal circumference couldbe considered as important selection criteria parameterswhile selecting young bulls for the purpose of frozen semenproduction to improve the frozen semen doses.